ANALISIS SISTEM PENGENDALIAN INTERNAL SEKOLAH DALAM MENGELOLA AKTIVA TETAP - Sari Sari; Warneri Warneri; Maria Ulfah (Universitas Tanjungpura, 2018)
AbstractThis study aims to determine how the school's internal control system in managing fixed assets in the form of school facilities and infrastructure and whether the implementation of internal controls are in accordance with applicable procedures. The research was conducted with qualitative approach. Data were obtained through in-depth interviews, observations, literature studies and triangulation. The data analysis techniques used are data reduction, data collection, data presentation, conclusion, and evaluation. The results showed that the control procedure was not fully in accordance with the regulations. Schools involve teachers in the implementation of control and school does not also have a vice principal who takes care of facilities and infrastructure so that the preparation and implementation of sound policies related to the management of fixed assets that are part of the facilities and infrastructure can not be done effectively for the achievement of goals. School internal control system in managing and recording fixed assets in the form of facilities and infrastructure delegated to the administration.Keywords: Internal Control System, Fixed Assets School